An application of Dijkstra’s algorithm model in finding shortest travel time in KLCC - Mohd Ghazali, Jamilah; Mohd Adnan, Raudah; Mohd Ismail, Nurul Izzati; Mohd Aripen, Nur Shahirah; Mohd. Shamsuri, Muhammad Izzwan Syahmi; Mustaffa, Nur Aqilah Zawani; Abdul Rahim, Nur Hanis (Penerbit UTHM, 2020)
Nowadays, traffic congestion or also known as traffic jammed is one of the common routing problems that usually occur on road networks. Routing problems becomes one of the big concern that most of the develop country must face including Malaysia.